Enhancing the temperature stability of PLA by compounding strategies. Issue 12 (18th September 2015) - Laske, Stephan; Ziegler, Wolfgang; Kainer, Markus; Wuerfel, Johannes; Holzer, Clemens
Abstract : The low thermal stability of polylactid acid (PLA) limits its use for various applications such as microwave‐ready dishes or hot beverage packaging. Furthermore, contained items might be damaged by occurring temperature peaks during transport (e.g., shipping container internal temperature exceeds 80°C) or other usage (e.g., car dashboard heated by sun). The aim of this study was the development of a PLA compound with an operating temperature above 100°C. Therefore, different formulations (e.g., stereocomplex of PLLA and PDLA, cross‐linking of PLA or use of commercial additives) were identified and compounds with varying conditions produced and tested regarding their thermal and mechanical properties. The results showed clearly possible routes for improving the thermal properties of PLA. Using such compounds respectively processing routes and additives helps to overcome one of the most significant problems when using PLA. The higher operating temperature of this biopolymer will lead to a wider field of application and will avoid shipping hazards. POLYM. ENG. SCI., 55:2849–2858, 2015. © 2015 Society of Plastics Engineers